Aplikasi Sistem Informasi Geografis Untuk Zonasi Kawasan Pertambangan Majenang-Bantarkawung - Yazid Fanani (PROMINE, 2016)
The position of Majenang-Bantarkawung region become important and strategic because has a lot ofmineral and coal resources. However, there is no effort in mining area regulation to optimalizationmanagement of mining resources who can useful for people prosperity. Mining zonation of Majenang-Bantarkawung make with weighting and scoring in determination of mining parameters thanprocessing the parameters with overlay method. The parameters are : Land height, Land elevation,Disaster-prone areas, Overburden thickness, Ground water, River area, Water infiltration areas,Forest areas and Agricultural area. According to overlay of 10 mining parameters, Majenang-Bantarkawung mining zonation can be divided into can be permitted to mined, can be permitted tomined with certain condition, and can’t be permitted to mined. Banyumas regency has 61 distributionof mining resources location. Cilacap regency has 75 distribution of mining resources location. Brebesregency has 53 distribution of mining resources location.